2009
DOI: 10.1111/j.1742-4658.2009.06940.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural characterization of novel mutations and genotype–phenotype correlation in 51 phenylalanine hydroxylase deficient families from Southern Italy

Abstract: Hyperphenylalaninemia (Online Mendelian Inheritance in Man ®database: 261600) is an autosomal recessive disorder mainly due to mutations in the gene for phenylalanine hydroxylase; the most severe form of hyperphenylalaninemia is classic phenylketonuria. We sequenced the entire gene for phenylalanine hydroxylase in 51 unrelated hyperphenylalaninemia patients from Southern Italy. The entire locus was genotyped in 46 out of 51 hyperphenylalaninemia patients, and 32 different disease‐causing mutations were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Although this is not always the case, similarly to other studies, we usually found a correlation between genotype and response to BH4; some studies establish a 76% correlation, others deem there to be good correlations, particularly in homozygotes, for nonresponsive mutations (Daniele et al 2009;Desviat et al 2004;Trefz et al 2009b;Zurfl€ uh et al 2008). …”
Section: Discussionsupporting
confidence: 87%
“…Although this is not always the case, similarly to other studies, we usually found a correlation between genotype and response to BH4; some studies establish a 76% correlation, others deem there to be good correlations, particularly in homozygotes, for nonresponsive mutations (Daniele et al 2009;Desviat et al 2004;Trefz et al 2009b;Zurfl€ uh et al 2008). …”
Section: Discussionsupporting
confidence: 87%
“…The lack of standardized methods for the classification of HPA phenotypes can complicate the interpretation of genotype-phenotype correlations (Daniele et al, 2009). In this study, we used pre-treatment plasma Phe levels for phenotypic classification.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been directed at determining which genotypes are likely to respond to BH 4 , with varying results (e.g. (11, 39, 52, 5458)).…”
Section: Bh4 Acting As a Pharmacological Chaperonementioning
confidence: 99%
“…100 – 200 μM). It is also interesting that patients expressing the L48S and/or I65T variants are reported as having highly variable responses to BH 4 therapy (54, 58, 65). …”
Section: The Vast Array Of Disease-associated Pah Variantsmentioning
confidence: 99%